Evaluation of LiDAR-derived river networks coarsening with spatial patterns preservation - Almeida, Ana Alice Rodrigues Dantas [UNESP]; Mendonça, Rafael Lopes; Silva, Natalia Maria Mendes; Paz, Adriano Rolim da (Elsevier, 2024)
Digital elevation models obtained from LiDAR surveys typically have a few meters or sub-meter resolution. DEM-derived products in such a fine resolution may not be desired for several circumstances, such as matching the resolution with other spatial datasets, preparing input data for hydrological models, and reducing the computational cost. This leads to DEM coarsening for further river network extraction. An alternative could be to derive the river flow paths in the original DEM resolution and use this information to obtain the coarser river networks (a procedure known as flow directions upscaling). This approach is the macroscale hydrology benchmark for deriving river networks with spatial resolution on the order of a few kilometers or even larger, based on the available DEM with tenths or hundreds of meters resolution. However, no study has applied this procedure for the change of scale involving fine-resolution LiDAR DEM. This research evaluated for the first time in literature a flow direction upscaling algorithm for deriving relatively coarse-resolution (30, 100, and 200m) river networks from very fine-resolution (1 m) flow paths obtained from LiDAR DEM. Two river basins of contrasting characteristics located in Northeast Brazil are studied. Results were evaluated through visual inspection, percentage within buffer (PWB) metrics, and river length comparison. It is shown that using an upscaling algorithm improves the ability of the coarse network to preserve river networks’ spatial patterns across multiple scale changes. Considering both basins, PWB ranged from 80% to 100% (average of 97%) for the upscaling procedure, while the DEM resampling resulted in PWB between 40% and 100% (average of 85%). A flow direction upscaling algorithm already used for macroscale hydrology proved helpful for the LiDAR-related shift in scale, outperforming the DEM resampling. Increasing the scale change augments the difference in performance between them, making the upscaling procedure more recommended. In addition, such an upscaling procedure provided drainage networks in the 100-m and 200-m resolutions with higher quality than the one obtained in the 30-m resolution directly from a globally available DEM.
Keywords: Digital elevation model; Digital terrain model; Drainage network; Flow direction upscaling; Spatial resolution